KLASIFIKASI MANGROVE BERDASARKAN KARAKTERISTIK HABITAT DI PANTAI MAROSI KABUPATEN SUMBA BARAT PROPINSI NUSA TENGGARA TIMUR - , Ni Kade Ayu Dewi Aryani, Dr. Erny Poedjirahajoe, MP ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objectives of the study are to analyze the variety of the mangrove and to find out the classification pattern of the mangrove habitat and also the influencing factors of the mangrove vegetation grouping. The parameters measured include growth and habitat factors. The growth parameter includes density and INP, while the habitat factors includes temperature